Temperature-Dependent Compatible and Incompatible Pollen-Style Interactions in Citrus clementina Hort. ex Tan. Show Different Transglutaminase Features and Polyamine Pattern - Aloisi, Iris; Distefano, Gaetano; Antognoni, Fabiana; Potente, Giulia; Parrotta, Luigi; Faleri, Claudia; Gentile, Alessandra; Bennici, Stefania; Mareri, Lavinia; Cai, Giampiero; Del Duca, Stefano (Frontiers in Plant Science, 2020)
In clementine, failure of fertilization can result in parthenocarpic fruit development, which has several advantages, such as seedless fruit, longer shelf-life, and greater consumer appeal. Recently, S-RNases have been identified in C. grandis, thus revealing that the self-incompatibility (SI) reaction relies on the S-RNase gametophytic mechanism. The fundamental role of environmental factors, mostly temperature, in determining the numbers of pollen tubes reaching the ovary is also well established in Citrus. In the present work, temperature-dependent pollen–pistil interactions in C. clementina were analyzed, focusing on several morphological aspects, as well as on polyamine (PA) content and the activity and distribution of transglutaminase (TGase), both reported to be involved in the SI response in pear and in pummelo. Results clearly indicate that temperature contributed to a different activation of the SI response, which occurs at optimal temperature of 25°C, but was by-passed at 15°C. TGase activity was stimulated during the SI response, and that it localized differently in the compatible and incompatible interaction: in compatible pollinated styles, TGase localized inside the style canal, while it was detected all around it in incompatible crosses. TGase localization and activity were congruent with the levels of soluble and insoluble conjugated PAs and with morphological evidences, which highlighted cell wall modification occurring as a result of SI.